PEMASANGAN PLANG ARAH JALAN SEBAGAI UPAYA PENINGKATAN FASILITAS DESA MEDALEM KECAMATAN MODO - Hamidah, Izzah; Panduwinata, Lifa Farida (Abimanyu : Jornal of Community Engagement, 2022)
The problem that occurs in Medalem Village is the lack of adequate facilities related to road signs. Signs also need to be made to make it easier for immigrants to enter Medalem Village. The plan installation program that will be carried out by the Lamongan 3 UNESA 2022 KKN group is carried out by making information signposts indicating directions, both directions to the village, the village head's house and the ranks of his apparatus, as well as certain other strategic locations. This community service activity begins by conducting field surveys or places where signage will be installed. After finding the location where the board will be installed, the next step is to make a plaque or board by buying the necessary tools and materials. After finishing making the plaque, it was continued with painting which was then continued with the installation of the plaque carried out by students assisted by the local community and produce 11 signboards. Keywords: Placing signs, Medalem Village